Exploring Corporate Strategy / Seventh Edition - Johnson Gerry; Scholes Kevan; Whittington Richard (Prentice Hall, 2006)
There is a full coverage of corporate governance, global strategies, core competences and resource-led strategies, networks and virtual organizations, internal market mechanisms, the impact of information technology and business process re-engineering. Preface, Introduction, Corporate Strategy: An Introduction, Strategic Management in Practice, Strategic Analysis, Analyzing the Environment, Resources and Competences and Strategic Capability, Stakeholder Expectations and Organizational Purposes, Strategic Choice, Bases of Strategic Choice, Strategic Options: Directions and Methods of Development, Strategy Evaluation and Selection, Strategy Implementation, Organization Structure and Design, Resource Allocation and Control, Managing Strategic Change, Index.